Optimization of Acid Wash Process on Activated Carbon with Variation of HCL Concentration at PT XYZ - Ardian, Fahny; Putra, Infantri; Nasuci, Figo S. M.; Wonua, Karla Jeclin; Purba, Janres Yoseva (Journal of Metallurgical Engineering and Processing Technology, 2024)
The acid wash process is used as a unit operation in the gold adsorption route with the primary objective of removing calcium carbonate, magnesium, and sodium salts from gold-rich carbon surfaces. In general, the use of HCl with an initial concentration of 3% (w/v) and immersion for 1 hour with 1 bed volume of acid can achieve calcium removal of more than 95% from the carbon surface. This research involved reducing the HCl concentration from 3% to varying concentrations between 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, and 2.75% with the aim is to optimize the use of HCl and increase economic efficiency in the acid wash process. Analysis of carbon activity data shows that the acid wash process does not have a significant effect on carbon reactivation. The research method involves collecting activated carbon samples in three types, namely Loaded Carbon (LC), Carbon After Wash (CAW), and Barren Carbon (BC). The samples were then analyzed using the Carbon hardness test to evaluate the level of impurities on the carbon surface, as well as the Carbon activity test to measure carbon absorption activity. Data on gold and silver recovery results was also collected from the elution process. The research results show that an HCl concentration of 2% provides optimal effectiveness in acid wash. At this concentration, desorption results were achieved that met the ADR KPI, confirming that acid wash did not significantly affect the gold desorption process. In addition, the acid wash efficiency at a concentration of 2% is close to the baseline value, indicating a good ability to clean carbon from impurities. In the context of this study, acid washing has been proven to be an effective method for cleaning activated carbon for gold adsorption. These findings provide an important contribution to improving the efficiency and quality of the gold absorption process.